Preparation of hierarchical flower-like nickel sulfide as hole transporting material for organic solar cells via a one-step solvothermal method. (August 2019) - Hilal, Muhammad; Han, Jeong In
Highlights: An easily and one-step solvothermal approach applied for the synthesis of hierarchical flower-like nickel sulfide (NiS). Addition of sulfur source with varies concentration significantly influenced the morphology of the NiS. The as-synthesized NiS has used as an anode interfacial layer for OSCs. The NiS_2.0 (NiS doped with 2.0 g of thioacetamide) based device achieved high efficiency than NiS_1.0, NiS_1.5, and NiS_2.5 based devices. OSCs based on NiS_2.0 demonstrated the best reproducibility as well as long-term environmental stability performances. Abstract: In this work, nickel sulfide (NiS) with a mesoporous network was prepared through a simple solvothermal approach. The influences of various contents of the sulfur source on the morphological changes were examined. Finally, the resultant NiS doped with various contents of sulfur were used as hole-transport layers (HTLs) for the application to organic solar cells (OSCs). Based on our knowledge of the implementation of OSCs, NiS-based HTLs are used for the first time in this paper. The OSCs developed with NiS_2.0 (NiS doped with 2.0 g of thioacetamide (sulfur source)) HTL showed a higher PCE response, at 2.28% than those fabricated with NiS_1.0 (NiS doped with 1.0 g of thioacetamide), NiS_1.5, (NiS doped with 1.5 g of thioacetamide), and NiS_2.5 (NiS doped with 2.5 g of thioacetamide), which only showed 1.38%, 1.88%, and 1.96%, respectively. Besides this improved photovoltaic response, it also demonstrated a superior reproducibility with a high degree of control over the environmental stability, i.e., 360 h, as compared to the bare PEDOT:PSS HTL-based OSCs, which showed just 240 h.